2009
DOI: 10.1177/0145482x0910300507
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Literacy Supports for Students who are Deaf-Blind or Have Visual and Multiple Impairments: A Multiple-case Study

Abstract: Seven classrooms of students with deaf-blindness or visual and multiple impairments were observed to document the emergent literacy supports that were present, including environmental characteristics, strategies, or activities. The findings revealed that the majority of classrooms used emergent literacy supports that were previously documented for students without disabilities. Implications for practice and suggestions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…All children benefit from literacy rich environments in the home and school. For children who are deafblind, this would include books in print and braille, auditory books, tactile books, accessible labeling of literacy materials, interactive software, and adapted commercial books [145]). In a 2019 study of emergent literacy materials and strategies in classrooms with students who are deafblind or with multiple disabilities and visual impairment, McKenzie found that teachers most often provided lessons on the daily news, morning circle, read alouds, and schedules.…”
Section: Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…All children benefit from literacy rich environments in the home and school. For children who are deafblind, this would include books in print and braille, auditory books, tactile books, accessible labeling of literacy materials, interactive software, and adapted commercial books [145]). In a 2019 study of emergent literacy materials and strategies in classrooms with students who are deafblind or with multiple disabilities and visual impairment, McKenzie found that teachers most often provided lessons on the daily news, morning circle, read alouds, and schedules.…”
Section: Literacymentioning
confidence: 99%
“…Supported writing activities, shared reading, and choice-making were offered less frequently. She suggested the need for literacy centers, accessible labeling, increased read alouds, opportunities to scribble, increased IEP objectives on literacy, and a learning media assessment to determine the best medium for presenting and producing literacy to each child [145].…”
Section: Literacymentioning
confidence: 99%
“…Comprehensive communication programming should address • • forms/modes, • • intents/functions, • • content/vocabulary, and • • context, including the establishment of activities and routines, the physical environment, communication partner skills, and pragmatics (Bashinski, 2011;Bruce, 2002;Crook, Miles, & Riggio, 1999a, 1999bGoodall & Everson, 1995;McKenzie, 2009;Miller, Swanson, Steele, Thelin, & Thelin, 2011).…”
Section: Communicationmentioning
confidence: 99%
“…All learners benefit from a literacy-rich environment (McKenzie, 2009 Learners who are deafblind require ample hands-on experiences to ensure that they understand the concepts expressed in books because they have few, if any, opportunities to gain information incidentally by listening or observing (Miles, 2005). The van Dijk Curricular Approach includes sequential memory strategies and symbolic instructional strategies to support literacy development through a child-guided approach (MacFarland, 1995).…”
Section: Supporting Literacy Developmentmentioning
confidence: 99%
“…In an observational study of the literacy experiences of students with deafblindness and multiple disabilities including visual impairments, McKenzie (2009) found that in the seven selfcontained classes observed, daily news, reading aloud, following activity schedules, and morning circle were the most common literacy activities. Observational studies of literacy instruction for students with severe disabilities have found that instruction might not reflect recommended practices.…”
Section: Documentation Of Literacy Practices For Students With Severementioning
confidence: 99%